Revisiting Code-Switching in TOEFL Instruction: Its Role In Facilitating Students’ Grammatical Proficiency - Arya Putra, Akbar Mandala; Bram, Barli; Ena, Ouda Teda (Universitas Sulawesi Barat, 2025)
This study examines the use of code-switching by lecturers in the TOEFL ITP preparation class. This class is mandatory for students of Siliwangi University to prepare to meet the graduation requirements. Code Switching is a strategy used to practice switching between two languages ​​in communication. The main function of this strategy is also a pedagogical goal. The study aims to analyze the types of code switching, their use and pedagogical goals. The theories used in this study include pedagogical goals, socio-linguistics and the needs and functions of language learning. The research method used is a quantitative method with survey data collection techniques to analyze simple regression of the relationship between lecturer's code-switching and grammatical understanding in TOEFL Preparation. The research was conducted in the political science department of Siliwangi University. The results of the study showed that there was an influence of 83.2% between the code switching variable and the ability to understand grammar in students majoring in political science at Siliwangi University. Therefore, the hypothesis can be accepted. The code-switching strategies used based on the results of the study include inter-sentential code-switching, intra-sentential code-switching, socio-cultural